2014
DOI: 10.1038/nrcardio.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

The role of heat shock proteins in atherosclerosis

Abstract: Atherosclerosis is a chronic, multifactorial disease that starts in youth, manifests clinically later in life, and can lead to myocardial infarction, stroke, claudication, and death. Although inflammatory processes have long been known to be involved in atherogenesis, interest in this subject has grown in the past 30-40 years. Animal experiments and human analyses of early atherosclerotic lesions have shown that the first pathogenic event in atherogenesis is the intimal infiltration of T cells at arterial bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 180 publications
5
132
0
4
Order By: Relevance
“…Since then several heat shock proteins have been postulated to be involved in atherosclerosis in a pro-or anti-atherosclerotic mode, although the mechanisms have not been clearly defined [25,35,36].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Since then several heat shock proteins have been postulated to be involved in atherosclerosis in a pro-or anti-atherosclerotic mode, although the mechanisms have not been clearly defined [25,35,36].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Atherosclerosis is a distinct case compared with typical autoimmune diseases because (1) the major autoantigen oxLDL is really a modified self-antigen or neo-self-antigen and (2) the oxLDL autoantigen, rather than playing a physiological function, is pathogenic and disease causing. There are also other autoantigens involved, such as heat shock protein 60,6,7 and the impact of other autoimmune diseases in promoting atherosclerosis such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) is well known. 8,9 The role of T cells and interferon-γ-secreting Th1 cells, in particular, as key drivers of plaque inflammation is well documented, and experimental approaches to dampen these responses by enhancing the activity of regulatory T cells are being tested.…”
Section: Immunity and Atherosclerosismentioning
confidence: 99%
“…At later stages of atherogenesis, intralesional T cells, macrophages, dendritic cells (DCs), and smooth muscle cells (SMCs) can also express HSP60, and the anti-HSP60 cellular immune reaction could therefore be perpetuated in situ. These experimentally and clinically proven findings represent the basis for the BAutoimmune Concept of Atherosclerosis^ (Wick et al 2004(Wick et al , 2014. This concept was first presented in 1992 and showed that normocholesterolemic rabbits immunized with mbHSP65 develop atherosclerotic plaques irrespective of their cholesterol levels Xu et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the last two decades, we and other laboratories have identified HSP60 as one of the most important antigens in early stages of atherosclerosis Wick et al 1995Wick et al , 2004. Proof of concept for the presence of antigenic mimicry has been thoroughly investigated in different animal models and humans (Wick et al 2014).…”
Section: Introductionmentioning
confidence: 99%